Antioxidant potential and phenolic content of ethanolic extract of selected malaysian plants - Rafat, A.; Philip, K.; Muniandy, S. (Research Journal Biotechnology, 2010)
This study evaluated the antioxidant capacity and total content of phenolic compounds in an ethanolic extract of some commonly consumed raw Malaysian plants. The antioxidant activities of the samples were measured by two different methods while the Folin-Ciocalteu reagent assay was used to estimate the phenolic contents of extracts. Cosmos caudatus extract showed the highest antioxidant potential followed by Centella asiatica, Oenanthe javanica, Euodia redlevi and Ocimum basilicum extracts respectively in both DPPH free radical scavenging activity and Superoxide Dismutase Activity Assays. Although the highest total phenolic content was found in Cosmos caudatus extract, there is no positive correlation between evaluated antioxidant activities and the phenolic contents Of examined plants.